2018
DOI: 10.1186/s13012-018-0762-5
|View full text |Cite
|
Sign up to set email alerts
|

Community health worker support to improve HIV treatment outcomes for older children and adolescents in Zimbabwe: a process evaluation of the ZENITH trial

Abstract: BackgroundCommunity health worker (CHW)-delivered support visits to children living with HIV and their caregivers significantly reduced odds of virological failure among the children in the ZENITH trial conducted in Zimbabwe. We conducted a process evaluation to assess fidelity, acceptability, and feasibility of this intervention to identify lessons that could inform replication and scale-up of this approach.MethodsField manuals kept by each CHW, records from monthly supervisory meetings, and participant data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Participants highlight vital factors such as secrecy and the socio-emotional consequences for all. These responses fit well with the findings of Chikwari, Simms, Busza, Dauya, Bandason, Chonzi, Munyati, Mujuru and Ferrand (2018) from an evaluation of community support programmes to improve HIV treatment outcomes for children and adolescents in Zimbabwe. The study established that refusal of HIV disclosure to children by parents creates multiple barriers, including obstruction of access and adherence to ART, and understanding at an early age of the impact of sexual activity on the spread of HIV.…”
Section: Parents Do Not Tell Their Children That They Have Hiv and This Makes It Difficult For Us And Other Community Members To Help Thesupporting
confidence: 78%
“…Participants highlight vital factors such as secrecy and the socio-emotional consequences for all. These responses fit well with the findings of Chikwari, Simms, Busza, Dauya, Bandason, Chonzi, Munyati, Mujuru and Ferrand (2018) from an evaluation of community support programmes to improve HIV treatment outcomes for children and adolescents in Zimbabwe. The study established that refusal of HIV disclosure to children by parents creates multiple barriers, including obstruction of access and adherence to ART, and understanding at an early age of the impact of sexual activity on the spread of HIV.…”
Section: Parents Do Not Tell Their Children That They Have Hiv and This Makes It Difficult For Us And Other Community Members To Help Thesupporting
confidence: 78%
“…In Ghana, a randomized trial demonstrated that a therapeutic communication and personalized interaction to promote disclosure integrated in HIV care visits resulted in increased disclosure at each study timepoint [ 34 ]. In Zimbabwe, a community health worker intervention supporting children with HIV and their caregivers with multiple components included assessments of pediatric disclosure and dedicated support for disclosure and discussions, and resulted in improved virologic suppression [ 35 ]. Further insights may be gleaned from the Amagugu intervention, a counselor-led home-based intervention supporting disclosure of maternal HIV status to HIV-uninfected children, given some anticipated common barriers driving caregiver hesitancies to disclose [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the availability of new medicines such as dolutegravir that offer a faster and sustained pathway to viral suppression (even among those who fail with older integrase inhibitors) will help, communitycentred activities to help support adherence to treatment are paramount [2,41]. Strategies that use peers and trained community health workers have been shown to produce retention rates and treatment outcomes on par with those reported in traditional healthcare delivery settings [42][43][44]. Viral load testing is critical to identify patients who do not have suppressed viral load and initiate adherence support or a switch to second-line or third-line therapy, as appropriate.…”
Section: Discussionmentioning
confidence: 99%